Spermatophore formation detected in Actinopteryx fucicola (Allibert) (Coleoptera Ptiliidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Several adults of A. facicola were collected on the Adriatic coast of Apulia (Southern Italy) by sifting masses of algae and Posidonia leaves. In late September, most females (about 80% out of 90 examined throughout) bore one spermatophore. This fills the genital chamber with a mass of amorphous material and includes a 50 μm large pear-like capsule. In some females examined on fresh preparations (n=12), the capsules contained a different number of spermatozoa. These are 120 μm long and spindle-like in their terminal tract; they are produced in a unpaired testis. Male genitalia exhibit a rich equipment of accessory glands, which are likely the source of the spermatophore envelope. No symptom of the preliminary formation of the spermatophore inside the male genital tracts was detected. Because spermatophores of A. fucicola include sperm, they can't be regarded as mere mating plugs to prevent sperm reflux and, therefore, they do correspond to the classical definition; because they are entirely moulded inside the female tracts, they agree with the "(3) female-determined type" of the most recent classification.
Keywords: structural features; moulding site; classification